Body Image Disturbance and Eating Disorder pada Atlet dan Non Atlet Wanita Member Club Fitness - Suci Marta Dewi; Anna Noordia; Yetty Septiani Mustar; Indra Himawan Susanto (Pusat riset dan Inovasi Nasional, 2025)
This study aims to identify and compare the prevalence of eating disorders and body image disturbances among female athletes and non-athlete members of fitness clubs. Given the rising societal emphasis on physical appearance and performance, young women are increasingly exposed to unrealistic body ideals, potentially increasing the risk of psychological issues such as body dissatisfaction and disordered eating behaviors. The research employed a descriptive quantitative design involving 100 women aged 18–25 years, consisting of 50 athletes actively participating in competitive sports and 50 non-athletes who regularly attend fitness clubs for general health purposes. Data were collected using two standardized instruments: the Body Image Concern Inventory (BICI) to assess levels of body image disturbance, and the SCOFF questionnaire to screen for symptoms of eating disorders. Results indicated that 34% of female athletes reported high levels of body image disturbance, compared to only 2% of non-athletes. Additionally, symptoms of eating disorders were present in 54% of athletes, while 14% of non-athletes showed similar tendencies. Statistical analyses using Mann-Whitney U and independent samples t-tests confirmed a significant difference between the two groups (p < 0.05), suggesting that athletes may be at a higher risk for developing these psychological issues. These findings underscore the psychological pressures faced by female athletes, who are often required to maintain specific body standards to meet performance expectations. The study highlights the urgent need for preventive measures, including psychological support services and educational interventions that promote healthy body image and eating habits. Implementing such programs in both sports and general fitness environments can help reduce the prevalence of these disorders and foster a healthier relationship with body image among young women.